Pendekatan Model Kognitif Dalam Pembelajaran Nahwu Dengan Analisis Psikolinguistik : Sebuah Systematic Literature Review - Hakami, fauzan (Riyahuna: Jurnal Pendidikan Bahasa Arab, 2024)
This study explores the application of cognitive models and psycholinguistic principles in the teaching of Arabic syntax (Nahwu) through a Systematic Literature Review (SLR). The research aims to identify effective teaching models that align with the cognitive dynamics of learners, addressing questions about how modern pedagogical approaches can enhance understanding of Arabic syntax. Using a structured methodology, this study examines relevant literature, evaluates its inclusion based on predefined criteria, and synthesizes data to uncover patterns and strategies. Key findings highlight the significant impact of Task-Based Learning (TBL) and Problem-Based Learning (PBL) on cognitive development, particularly in fostering retention, comprehension, and practical application of Nahwu. The study emphasizes the integration of psycholinguistics in addressing learners' cognitive needs, suggesting the use of engaging and culturally relevant teaching materials to increase motivation and attention. This research concludes that adopting TBL and PBL within a psycholinguistic framework can significantly improve the efficiency and effectiveness of Arabic syntax teaching. It also underscores the need for further exploration of technology's role in enhancing interactive and personalized learning experiences.